EFFECT OF ACTIVE PLAY METHOD ON PRE-SCHOOL CHILDREN SOCIAL AND FINE MOTOR DEVELOPMENT - Riska Arsita Harnawati; Evi Zulfiana; Juhrotun Nisa (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
Playing activities made children enjoy themselves and are carried out independently and involve various aspects to respond to and develop their social. This study aimed to determine the effect of active play on preschool-age children's social and fine motoric development at Miftahul Ulum Kindergarten, Tegal Regency. The design used in this research was a pre-experimental design with a pre-post test design, which aimed to determine the effect of independent variables on the dependent variable. Data analysis was performed using non-parametric statistical tests using the Wilcoxon test. The study results obtained p = 0.016, which shows active play affects preschool-age children's social and fine motoric development. Thus, this study's results can be used to increase knowledge and knowledge about the effect of active play on pre-school children's social development. Keywords: Active Play, Social Development.